Integration of modernist or postmodernist photographers into a course on photography - Iwan Zahar (2011)
The dispute has been long whether photographic lecturers should integrate the history of photography into a course on photography. The photographic lecturers should discuss photographic theory deeply, by introducing photographers such as Henry Cartier Bresson, Cindy Sherman, Barbara Kruger etc to students. Most of the photographic lecturers were more interested in teaching photographic techniques than photographic theory. Survey research was designed to investigate 50 students in fifth semester, on September to December 2010, at Tarumanagara University, Jakarta. Structured observations, written questionnaires (a pre test- and post test), and oral questionnaires, interviewed were used to gather in depth data of students ‘learning on how to interpret modern and post modern photographs. Photographic lecturer used Barrett’s photo criticism model as the latest model and problem-based learning as teaching methods to integrate the history of photography into photography course. The research used aesthetic exemplars in the form of modernist and postmodernist photographers, or from Alfred Stieglitz to Cindy Sherman. Most of the students were easily to relate with modernist photographers compared to postmodernist photographers. The students were unfamiliar with subject matter, theme, and photos presentation, thus they become difficult interpret postmodernist photos. Moreover, students were more interested in photographic techniques which were used by modernist photographers. Even though, Tarumanagara students lived in Jakarta, but they were not acquainted with postmodernist theme such as feminist, sexual orientation, gender, and multiculturalism.